Sugarcane cutting work, risks, and health effects: a literature review - Leite, Marceli Rocha; Trevisan Zanetta, Dirce Maria; Trevisan, Iara Buriola [UNESP]; Burdmann, Emmanuel de Almeida; Santos, Ubiratan de Paula (Revista De Saude Publica, 2018)
OBJECTIVE: Describe the main work risks for sugarcane cutters and their effects on workers' health. METHODS: Critical review of articles, with bibliographic research carried out in the PubMed, SciELO Medline, and Lilacs databases. The following keywords were used: sugarcane workers, sugarcane cutters, sugarcane harvesting, cortadores de cana-de-acucar, and colheita de cana-de-acucar. The inclusion criteria were articles published between January 1997 and June 2017, which evaluated working conditions and health effects on sugarcane cutters. Those that did not deal with the work impact of cutting burned and unburnt sugarcane in the cutter's health were excluded. The final group of manuscripts was selected by the lead author of this study and reviewed by a co-author. Disagreements were resolved by consensus using the predefined inclusion and exclusion criteria and, where necessary, the final decision was made by consulting a third co-author. RESULTS: From the 89 articles found, 52 met the selection criteria and were evaluated. Studies have shown that cutters work under conditions of physical and mental overload, thermal overload, exposure to pollutants, and are subject to accidents. The main effects observed were respiratory, cardiovascular, renal, musculoskeletal, heat stress, dehydration, genotoxic, and those due to accidents. CONCLUSIONS: Work on the manual cutting of sugarcane, especially of burned sugarcane, exposes workers to various risks, with different health impacts. Risk reduction for exposure to pollution and thermal and physical overload is required as a measure to preserve the health of the worker.
Keywords: Rural Workers; Health Status; Working Conditions; Occupational Risks; Occupational Health; Review